Antimicrobial Biocomposites Fiber‐Welded with Lignocellulose Containing Silver Nanoparticles. Issue 5 (17th May 2022) - Shen, Hongchen; Gulbrandson, Anders J.; Park, Seok; Li, Mengqiao; Shuai, Danmeng; Trulove, Paul C.; Durkin, David P.
Abstract : Natural Fiber Welding The anchor is printed on cellulose paper using ionic liquid ink containing silver nanoparticle laden lignocellulose. The study in article number 2100872 by David P. Durkin and co‐workers shows how natural fiber welding can transform functional powders into anti‐microbial and anti‐biofilm textiles, which may be considered for personal protective equipment.